2014
DOI: 10.1097/rct.0000000000000118
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Evaluation of Sciatic Nerve Crush Injury Using Diffusion Tensor Imaging

Abstract: The changes in FA and λ⊥ of distal portions of injured sciatic nerves correlate well with functional recovery and histology. Therefore, FA and λ⊥ of distal portions of injured sciatic nerves can be used as a marker to monitor Wallerian degeneration and regeneration of crushed sciatic nerves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Alterations in DTI-derived metrics are believed to reflect changes in peripheral nerve microstructure and overall ‘nerve health’ [ 12 ]. Recent studies have demonstrated good correlation between DTI and functional and histologic parameters in assessing nerve regeneration in rodent models [ 8 , 13 ] and rabbit models [ 14 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Alterations in DTI-derived metrics are believed to reflect changes in peripheral nerve microstructure and overall ‘nerve health’ [ 12 ]. Recent studies have demonstrated good correlation between DTI and functional and histologic parameters in assessing nerve regeneration in rodent models [ 8 , 13 ] and rabbit models [ 14 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated that this technique can also be used in the study of peripheral nerves (8) , although we found no studies with an emphasis on the specific evaluation of sciatic nerve abnormalities in humans. Recent experimental studies involving animal models of crush injury and sciatic nerve traction injury showed that DTI tractography, using routine clinical 1.5 T MRI scanners, is a promising tool in the assessment of sciatic lesions (9,10) . In those studies, DTI was able to differentiate between nerves with nerve damage and control group nerves.…”
Section: Introductionmentioning
confidence: 99%
“…The pattern identified here is similar to recent DTI studies at lower field strength in patients with CTS 24 , 36 , 37 or other peripheral neuropathies. 31 , 38 , 39 Reduced FA and increased RD are also the predominant findings in experimental nerve injury models, where they correlate with histological markers of axon and myelin degeneration, 40 42 or the presence of inflammation-induced edema. 43 In humans, correlation of diffusion parameters with electrodiagnostic parameters thought to reflect axonal damage or demyelination reveal conflicting outcomes.…”
Section: Discussionmentioning
confidence: 95%